Bioactivity of Endophytic Fungal Extract Isolated from Purun (Eleocharis dulcis (Burm.f.) Trin. ex Hensch) - Oktiansyah, Rian; Pratiwi, Mardiyah; Kharisma, Sully Pudja; Fauzan, Ahmad Rizki; Utami, Riza; Amelia, Dea; Noviyanto, Noviyanto; Nasution, Sakinah Salman Ahmad (Department of Biology, Faculty Mahematics and Natural Sciences, University of Jember, 2024)
The study investigates the bioactivity of endophytic fungi isolated from Eleocharis dulcis (Burm.f.) Trin. ex Hensch., focusing on their potential as alternative sources of bioactive compounds. E. dulcis, a plant commonly found in wetland ecosystems, has traditionally been used for its medicinal properties. However, the massive extraction of the plant may lead to ecological imbalance, prompting the exploration of endophytic fungi as a sustainable alternative. The objective of this research is to isolate, identify, and evaluate the antimicrobial and antioxidant properties of endophytic fungi from Eleocharis dulcis. Endophytic fungi were isolated aseptically, followed by morphological identification. Antioxidant and antimicrobial assays were conducted to assess the bioactivity of the fungal extracts. Antioxidant activity was evaluated using the DPPH method, while antibacterial activity was assessed using the disc paper diffusion method. The results revealed that several isolates (from leaves: LP1 – LP6, from root: RP1 – RP3) exhibited significant antimicrobial activity against Escherichia coli and Staphylococcus aureus, with Penicillium spp. and Cladosporium spp. showing the highest levels of bioactivity. Additionally, all fungal isolates demonstrated very strong antioxidant activity, with most achieving an IC50 below 20 µg/mL. In conclusion, the findings suggest that endophytic fungi from E. dulcis represent a valuable source of bioactive compounds with potential applications in pharmaceuticals. Further research is required to isolate and characterize the active compounds, as well as to evaluate their efficacy through in vivo studies